2018
DOI: 10.1101/252338
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brain network segregation and integration during an epoch-related working memory fMRI experiment

Abstract: The characterization of brain subnetwork segregation and integration has previously focused on changes that are detectable at the level of entire sessions or epochs of imaging data. In this study, we applied time-varying functional connectivity analysis together with temporal network theory to calculate point-by-point estimates in subnetwork segregation and integration during an epoch-based (2-back, 0-back, baseline) working memory fMRI experiment as well as during resting-state. This approach allowed us to fo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 62 publications
0
9
1
Order By: Relevance
“…One possible explanation for the call for wider networks to resolve conflict during drowsiness would be the need for involvement of extended neural resources to solve the same task, as seen previously in older adults when they are matched in performance to younger adults (Reuter-Lorenz and Cappell, 2008;Spreng et al, 2017). Convergent evidence is drawn from cognitive control studies, where the frontoparietal control networks are further recruited with higher cognitive load (Liang et al, 2016;Fransson et al, 2018), tasks possibly reflecting the higher need for neural resources. In other words, the brain's capacity for plasticity allows for the expansion of conflict networks in cases where another element in the system (e.g.…”
Section: Discussionmentioning
confidence: 82%
“…One possible explanation for the call for wider networks to resolve conflict during drowsiness would be the need for involvement of extended neural resources to solve the same task, as seen previously in older adults when they are matched in performance to younger adults (Reuter-Lorenz and Cappell, 2008;Spreng et al, 2017). Convergent evidence is drawn from cognitive control studies, where the frontoparietal control networks are further recruited with higher cognitive load (Liang et al, 2016;Fransson et al, 2018), tasks possibly reflecting the higher need for neural resources. In other words, the brain's capacity for plasticity allows for the expansion of conflict networks in cases where another element in the system (e.g.…”
Section: Discussionmentioning
confidence: 82%
“…While not tested explicitly in this study, the implication for this result is that the topological signature of the brain could provide important constraints on the manner in which different neural regions could respond across unique cognitive contexts. Previous research has found a wealth of evidence regarding the importance of states of more integration and/or segregation while performing cognitive tasks (Bassett et al, 2015; Cohen & D’Esposito, 2016; Cole et al, 2013; Fransson et al, 2018; Hearne et al, 2017; Shine et al, 2016). Increased excitability of local stimulation has a complex effect on the topological reconfiguration of the network.…”
Section: Discussionmentioning
confidence: 99%
“…Despite promising links to behaviour, the neuroscientific interpretation of these fluctuations however remains an open scientific question (Shine & Poldrack, 2018). There is evidence to suggest that the brain can shift towards integration during task performance (Cohen & D’Esposito, 2016; Shine et al, 2016), while others have argued that the interplay of a subset of segregated systems is also crucial (Fransson et al, 2018). These lines of inquiry suggest that the dynamic balance between integration and segregation is perhaps the most critical feature of whole-brain organization (Park & Friston, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This competition among modules in brain functional organization is dynamically adjusted to support cognitive functions that involve alterations in functional segregation and integration 13,15 and allows highly flexible information communication across local and global scales. Indeed, different cognitive tasks have heterogeneous demands regarding segregated and integrated brain network processes 13,16,[43][44][45][46] . For example, a previous study found increased segregation underlying successful motor execution and increased integration underlying successful working memory 8 .…”
Section: Decreased Brain Network Global Integration At the Task Statementioning
confidence: 99%